Copper diffusion in Ti–Si–N layers formed by inductively coupled plasma implantation - Xu, S. (2012)
Ternary Ti–Si–N refractory barrier films of 15 nm thick was prepared by low frequency, high density, inductively coupled plasma implantation of N into TixSiy substrate. This leads to the formation of Ti–N and Si–N compounds in the ternary film. Diffusion of copper in the barrier layer after annealing treatment at various temperatures was investigated using time-of-flight secondary ion mass spectrometer (ToF-SIMS) depth profiling, X-ray diffractometer (XRD), field emission scanning electron microscopy (FESEM), energy dispersive X-ray (EDX) and sheet resistance measurement. The current study found that barrier failure did not occur until 650 °C annealing for 30 min. The failure occurs by the diffusion of copper into the Ti–Si–N film to form Cu–Ti and Cu–N compounds. FESEM surface morphology and EDX show that copper compounds were formed on the ridge areas of the Ti–Si–N film. The sheet resistance verifies the diffusion of Cu into the Ti–Si–N film; there is a sudden drop in the resistance with Cu compound formation. This finding provides a simple and effective method of monitoring Cu diffusion in TiN-based diffusion barriers.